Impact of maternal overweight and obesity on milk composition and infant growth. Issue 3 (19th February 2020) - Ellsworth, Lindsay; Perng, Wei; Harman, Emma; Das, Arun; Pennathur, Subramaniam; Gregg, Brigid
Abstract: Overweight and obesity (OW/OB) impact half of the pregnancies in the United States and can have negative consequences for offspring health. Studies are limited on human milk alterations in the context of maternal obesity. Alterations in milk are hypothesized to impact offspring development during the critical period of lactation. We aimed to evaluate the relationships between mothers with OW/OB (body mass index [BMI] ≥25 kg/m 2 ), infant growth, and selected milk nutrients. We recruited mother–infant dyads with pre‐pregnancy OW/OB and normal weight status. The primary study included 52 dyads with infant growth measures through 6 months. Thirty‐two dyads provided milk at 2 weeks, which was analysed for macronutrients, long‐chain fatty acids, and insulin. We used multivariable linear regression to examine the association of maternal weight status with infant growth, maternal weight status with milk components, and milk components with infant growth. Mothers with OW/OB had infants with higher weight‐for‐length (WFL) and BMI Z ‐scores at birth. Mothers with OW/OB had higher milk insulin and dihomo‐gamma‐linolenic, adrenic, and palmitic acids and reduced conjugated linoleic and oleic acids. N6 long‐chain polyunsaturated fatty acid (LC‐PUFA)‐driven factor 1 was associated with higher WFL, lower length‐for‐age (LFA), and lower head circumference‐for‐age Z ‐scores change from 2 weeks to 2 months in human milk‐fed infants, whereas N6 LC‐PUFA‐driven factor 5 was associated with lower LFA Z ‐score change. Human milk composition is associated with maternal pre‐pregnancy weight status and composition may be a contributing factor to early infant growth trajectory.